Compartment Syndrome- Controversies and where are we Today - Shetty, M. Shantharam; Kumar, Ajith; Shetty, Lathika; Palanivel, Anbuchezhian (Journal of Health and Allied Sciences NU, 2017)
Compartment Syndrome in Orthopedic practice is a night mare and has to be diagnosed and treated as an emergency to save the function of the limb. Importance of different criteria of early diagnosis, compartment pressure measurement and immediate fasciotomy are the controversies even today. The review emphasizes the importance of these concerns.DefinitionCompartment syndrome occurs due to an increased interstitial tissue pressure inside a closed 1 space especially in an osseo-fascial compartment , should be treated as an acute emergency.